Representations of conflict in Greek pottery - Saad Hafid Obaid (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
Greek pottery is among the oldest arts and crafts known to humankind, initially linked to daily and functional needs, and later becoming enduring, imbued with aesthetic and symbolic values. Greek pottery was distinguished by its diverse styles and renowned techniques that emerged throughout different eras. Artists excelled in shaping the clay, employing firing and coloring techniques to produce high-quality pottery pieces. The graphic designs and patterns on pottery vessels reflected various aspects of Greek life, including economic, commercial, social, and political ideas. Initially simple designs based on clustered elements, they later incorporated human and animal motifs with symbolic and functional significance. This has contributed to the study of conflict patterns in the decorative designs of Greek pottery, revealing the details and artistic techniques used by Greek artists in producing these works, and their role in uncovering aspects of ancient civilization.